School Strategy in Strengthening Students' Character Education Through Culture at Ahmad Yani Elementary School, Malang City and Langdungsari 01 Elementary School, Malang Regency - Sindy Mulia Eka; Nurul Ulfatin; Asep Sunandar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the strategies for strengthening students' character education through school culture at SDIT Ahmad Yani in Kota Malang and SDN Langdungsari 01 in Kabupaten Malang. Character education is implemented by integrating Islamic values and national culture through programs such as congregational prayers, joint prayers, flag ceremonies, and national day celebrations. The objective of these programs is to cultivate students with noble character, national awareness, and preparedness for global challenges with a strong national identity. The research uses a qualitative approach with a case study method, involving participatory observation, in-depth interviews, and document analysis. Findings reveal that SDIT Ahmad Yani applies Islamic character education through routine practices like dhuha and congregational prayers and extracurricular activities related to the Qur'an, which strengthen students' moral and spiritual foundations and support the development of noble character according to the concept of ulul albab. At SDN Langdungsari 01, national character education is implemented through flag ceremonies, singing national songs, and introducing national history, fostering a sense of patriotism and appreciation for Indonesia’s cultural diversity. Both schools integrate Islamic and national values to create outstanding students with strong character and national consciousness, demonstrating that character education programs through school culture effectively develop intelligent, morally upright students with a robust national identity.